Significados do trabalho para servidores técnicos e administrativos de uma instituição pública de ensino superior no interior paulista - Varge, Caroline Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The global context of political, economic, technological, and social changes affects directly work characteristics, mainly models of organization and management, and it brings consequences often harmful to workers. Therefore, studies about questions related to work are frequently required, in relation either with its contributions for societal development or with dangers leading to problems in workers' health, among other issues. It is also necessary to understand the presentation and relationship of workers in their work environment. In order to investigate these aspects related to work in public service, a quantitative and qualitative research was performed based on theoretical method approach in socio-historical Psychology. Its purpose was to know meanings of work for public administrative and technical employees of a higher education institution. The participants of this research are employees from four university units of Botucatu campus. Data collection was performed in two stages: the first one with collection of social and demographic characteristics of subjects, and the second one with questionnaire designed by the researcher, which was answered by 150 workers. Interviewed subjects had a positive concept of work, in overall and positive concept of public staff occupation, in particular. Meanings of being a public employee are described as satisfaction, social responsibility, work stability, contribution for the institution to achieve their goals, and aspects of work relationship. Such results suggest difference in the occupation of those public workers compared with the general situation of workers in the current social and economic context. It may benefit the preservation health at work. A following study deepening the knowledge of meanings of work for public employees is expected

O contexto mundial de mudanças políticas, econômicas, tecnológicas e sociais influencia diretamente nas características do trabalho, sobretudo nos modos de organização e gestão, trazendo consequências muitas vezes danosas aos trabalhadores. Sendo assim, cada vez mais se tornam necessários os estudos de questões relativas ao trabalho, tanto no que tange às suas contribuições com o desenvolvimento da sociedade, como os agravos que podem incorrer, entre outros, em problemas à saúde dos trabalhadores, sendo necessário compreender também a inserção e relação dos trabalhadores com seu trabalho. Para investigar estes aspectos no que tange ao trabalho no serviço público, foi realizada uma pesquisa quantitativa e qualitativa, de base teórico-metodológica na Psicologia Sócio-histórica, com o objetivo de conhecer significados de trabalho para servidores públicos técnico-administrativos de instituição de ensino superior. Os participantes da pesquisa são servidores de quatro unidades universitárias do câmpus de Botucatu. A coleta de dados foi realizada em duas etapas: a primeira com levantamento das características sociodemográficas da população e a segunda com aplicação de questionário elaborado pela pesquisadora, o qual foi respondido por 150 trabalhadores. Os entrevistados apresentaram uma concepção positiva do trabalho, em geral, e da posição de servidor público, em particular. Destacam-se como significados de ser servidor público satisfação, responsabilidade social, estabilidade, contribuição com a instituição para alcance de seus objetivos e aspectos de relacionamento no trabalho. Tais resultados sugerem diferença na posição destes servidores públicos comparando-se à situação geral dos trabalhadores no contexto sócio-econômico atual, podendo favorecer a preservação da saúde no trabalho. Indica-se a continuidade de estudo que aprofunde no conhecimento dos sentidos do trabalho para...
Meanings of work for administrative and technical employees of a higher education public institution in midwestern São Paulo
Keywords: Saúde do trabalhador; Saúde pública; Ensino superior; Servidores públicos; Public officers; Public health